Analisis pendapatan berdasarkan pola konsumsi nelayan jaring insang (gill net) di Desa Bajo Indah Kecamatan Soropia Kabupaten Konawe - Lorensia, Lonika; Yusuf, Sarini; Rosmawati (Jurnal Sosial Ekonomi Perikanan, 2021)
This study aims to determine the consumption pattern of gill net fisherman and to determine the amount of income based on the consumption pattern of gill net fisherman in Bajo Indah Village, Soropia District Konawe Regency, from March to April 2020. This study used the census method with 16 respondents. The research variables measured and observed were food consumption patterns, non-food consumption and additional comsumption by fisherman. The data abtained were analysed using qualitative descriptive. The results ot this study indicate that fishermanʼs income is calculated based on the expenditure pattern of their consumption with an average total expenditure of Rp46.622.625/year. The pattern of comsumption expenditure shows that the average consumption expenditure for fisherman food is Rp21.533.563/year the average comsumption expenditure for non-food is Rp24.784.063/year and additional expenditure is Rpp305.000/year.